THE METHODS OF TEACHING ENGLISH LANGUAGE IN NON PHILOLOGICAL - Hudayberdieva Laziza Sanjarovna (Journals Park Publishing, 2022)
This article talks about the methods of teaching English in universities. These teaching methods are more used in practical classes, and have good results.
Keywords: student, language, classroom, teaching.